Chemical, Microbiological and Sensory Characteristics of Wader Fish (Rasbora argyrotaenia) Joruk During Fermentation - Dyah Koesoemawardani; Nida Rianda Nabila; Samsul Rizal; Suharyono AS; Esa Ghanim Fadhallah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Joruk is a fermented fish product typical from East Ogan Komering Ulu, South Sumatra. This study aims to determine the chemical, microbiological, and sensory properties of the joruk during fermentation, as well as to get the right fermentation time for joruk production. Research was performed by preparing joruk using wader fish. Observations included pH, total lactic acid, water content, and total volatile base (TVB), total molds and yeasts, total microbes, and total lactic acid bacteria (LAB). Furthermore, the best treatment was observed for sensory properties and protein content. Results showed that during fermentation there was a decrease in the pH value, total mold, total microbes, and water content, while the total amount of lactic acid, LAB, and TVB increased. The best treatment was obtained on joruk stored on the 10th day of fermentation with a pH value of 6.33, total lactic acid 9.48%, water content 67.74%, TVB 93.88%, and total LAB, total mold/yeast, and total microbes was respectively 10.46, 7.21, and 12,13 log CFU/g. Sensory properties for raw joruk was brown with 6.2 scale, fishy (6.4), and intact appearance (5.1). Sensory properties for cooked joruk was brown (4.2), fishy (6.7), salty taste (3.1), sour taste (8.4), and incomplete appearance (2.8).Keywords: Characteristic, joruk, wader fish, protein, TVB